Answer:
[tex]\frac{2x}{x+5}[/tex]
Step-by-step explanation:
We are given the following two functions and we are to find [tex] \frac {f} {g} (x) [/tex]:
[tex] f(x) = 4x + 6x [/tex]
[tex] g(x) = 2x^2 + 13x +15 [/tex]
Factorizing both the functions before solving them further.
[tex] f(x) = 4x + 6x = 2x (2x+3) [/tex]
[tex] g(x) = 2x^2 + 13x + 15 = x^2+3x+10x+15 = (x+5) (2x+3) [/tex]
Finding [tex] \frac {f} {g} (x) [/tex]:
[tex] \frac {f} {g} (x) [/tex] [tex]=\frac{2x(2x+3)}{(x+5)(2x+3)} = \frac{2x}{x+5}[/tex]